2014
DOI: 10.1097/inf.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Parapneumonic Pleural Effusions Caused by Streptococcus pneumoniae Serotype 3 in Children Immunized with 13-Valent Conjugated Pneumococcal Vaccine

Abstract: During 2012, Streptococcus pneumoniae serotype 3 was identified by polymerase chain reaction in 15 out of 20 (75%) pleural fluid specimens from children with pneumococcal pneumonia complicated by parapneumonic pleural effusion in Greece. One-third of these children had been immunized with the 13-valent conjugated pneumococcal vaccine after the age of 12 months, according to the national immunization schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 9 publications
3
21
1
2
Order By: Relevance
“…The majority of parapneumonic effusions in our study were found to be caused by serotype 3, which has recently been reported to be associated with empyema even in children immunized with PCV13 in Greece [10]. Serotype 19A was the second most frequently detected serotype by PCR in this study.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The majority of parapneumonic effusions in our study were found to be caused by serotype 3, which has recently been reported to be associated with empyema even in children immunized with PCV13 in Greece [10]. Serotype 19A was the second most frequently detected serotype by PCR in this study.…”
Section: Discussionsupporting
confidence: 65%
“…This will allow the effectiveness of PCV13 and the need for future development of new pneumococcal vaccines to be assessed using much more comprehensive information than is currently available using culture-based surveillance. Molecular surveillance will also be important to determine whether or not S. pneumoniae serotype 3 pneumonias with parapneumonic effusion are effectively prevented by the use of PCV13, as this serotype has caused infection in some patients immunized with PCV13 [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] PCV13 failure to offer protection from parapneumonic effusion due to serotype 3 was also noted in a catch-up program with one dose of PCV13 administered after the 2nd year of life, whereas one child had received two doses, the first at the age of 21 months. [24] The failure of PCV13 in cases of parapneumonic empyema due to serotype 3 does not predict the inability of the vaccine to reduce the incidence of CAP cases due to serotype 3, as parapneumonic effusions represent only a subset of complicated pneumonias with an underlying mechanism which still remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Reports of vaccine failure from PCV13 have been documented most frequently for serotype 3, 2, 3 however to date this has not been described for other serotypes. We report a case of bacteremic pneumococcal pneumonia due to serotype 19A in a child who had received four doses of PCV13.…”
mentioning
confidence: 99%